Helminth Immunomodulation in Autoimmune Disease - Smallwood, Taylor B.; Giacomin, Paul R.; Loukas, Alex; Mulvenna, Jason P.; Clark, Richard J.; Miles, John J. (Frontiers in Immunology, 2017)
Helminths have evolved to become experts at subverting immune surveillance. Through potent and persistent immune tempering, helminths can remain undetected in human tissues for decades. Redirecting the immunomodulating “talents” of helminths to treat inflammatory human diseases is receiving intensive interest. Here we review therapies using live parasitic worms, worm secretions and worm-derived synthetic molecules to treat autoimmune disease. We review helminth therapy in both mouse models and clinical trials and discuss what is known on mechanisms of action. We also highlight current progress in characterising promising new immunomodulatory molecules found in excretory/secretory products of helminths and their potential use as immunotherapies for acute and chronic inflammatory diseases.